Phenolic Compounds from Allium schoenoprasum, Tragopogon pratensis and Rumex acetosa and Their Antiproliferative Effects - Petr Saha; Otakar Rop; Pavel Valasek; Petr Humpolicek; Jiri Mlcek; Zdenka Kucekova (Molecules, 2011)
Experimental studies have shown that phenolic compounds have antiproliferative and tumour arresting effects. The aim of this original study was to investigate the content of phenolic compounds (PhC) in flowers of Allium schoenoprasum (chive), Tragopogon pratensis (meadow salsify) and Rumex acetosa (common sorrel) and their effect on proliferation of HaCaT cells. Antiproliferative effects were evaluated in vitro using the following concentrations of phenolic compounds in cultivation medium: 100, 75, 50 and 25 µg/mL. Phenolic composition was also determined by HPLC. The results indicate that even low concentrations of these flowers’ phenolic compounds inhibited cell proliferation significantly and the possible use of the studied herb’s flowers as sources of active phenolic compounds for human nutrition.